2010
DOI: 10.1007/s10689-010-9409-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-truncating hMLH1 variants identified in Slovenian gastric cancer patients are not associated with Lynch Syndrome: a functional analysis report

Abstract: Hereditary non-polyposis colorectal cancer is the most common known genetic syndrome that predisposes to various types of cancer including gastric cancer and occures mainly due to pathogenic germline mutations in DNA mismatch repair (MMR) genes, such as MLH1, MSH2 and MSH6. Impaired MMR activity can lead to microsatellite instability (MSI) in tumor tissues. Interpreting the pathogenic significance of identified mutations in MMR genes, especially missense alterations and short in-frame deletions and insertions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Many laboratories have analysed its genotype-phenotype correlation, with conflicting results. Some studies claim MLH1 K618A does not affect protein expression or MMR activity and can be found in healthy individuals as frequently as in patients with LS 25–30. Other studies suggest MLH1 K618A to be a low penetrance mutation 31–38…”
Section: Discussionmentioning
confidence: 99%
“…Many laboratories have analysed its genotype-phenotype correlation, with conflicting results. Some studies claim MLH1 K618A does not affect protein expression or MMR activity and can be found in healthy individuals as frequently as in patients with LS 25–30. Other studies suggest MLH1 K618A to be a low penetrance mutation 31–38…”
Section: Discussionmentioning
confidence: 99%
“…We also assessed two of the variants, which were described for the first time in our study (Hudler et al, 2004). We have shown that identified missense mutations were not causally associated with MSI-H phenotype in analysed gastric cancer tissues (Vogelsang & Komel, 2010).…”
Section: Mutational Impairment Of Mmr Activity and Pathogenic Signifimentioning
confidence: 96%